Stakeholders’ Consumption of Agricultural Injury Reports from News Media: A Six-Year Analysis of Website Usage and Visitor Analytics - Richard Burke; Matthew Pilz; Emily Redmond; Serap Gorucu; Bryan Weichelt (Safety, 2021)
AgInjuryNews.org is a news report-based, online sentinel surveillance dataset that has provided publicly available news and media reports of agricultural injuries since early 2015. In the 6 years since its inception, AgInjuryNews.org has hosted 12,897 unique visitors and has collected 997 user account registrations. New users from geographic areas home to NIOSH-funded agricultural research centres were most prominent, with these centres returning in larger numbers, comparatively. Users were acquired mostly through web searches, collaborations with other agencies, and paid Facebook.com advertisements. Paid advertisements recruited 3792 visitors; however, retention, registrations, and on-site engagement from this source was low. This analysis shows that data consumption on AgInjuryNews.org is steadily growing. Similar self-hosted programs that provide data or digital resources to agricultural safety and health stakeholders should consider the integration of auditing and analytics tracking, including user registrations.